MaPS: um framework para aplicações colaborativas em ambientes de computação ubíqua - Nino, Cássia Pereira (Universidade do Vale do Rio do Sinos, 2009)
Over the years, computers have grown in importance in supporting collaboration. Previously used solely as tools in already established processes, today, beyond that purpose, they also have a hole of fostering new and unforeseen forms of collaboration. As a fundamental objective, collaborative systems intended to meet the whole set of demands of a collaboration, what means, under the terms of the 3C Model, to provide tools and features that address communication, coordination and cooperation between parts. Nevertheless, new technologies are allowing to further increase the workspace of these systems, bringing collaboration support beyond the three traditional divisions stated at the 3C Model and towards acting in preliminary stages, such as the search for users and resources. This is possible, for instance, as we are immersed in a scenario of ubiquitous computing. Using the characteristics that this environment provides, such as mobility and context-awareness, it is possible to improve the processes of collab
MaPS: a framework for collaborative applications in ubiquitous computing environments
Keywords: colaboração ubíqua; computação ubíqua; frameworks; aplicações colaborativas; ubiquitous collaboration; ubiquitous computing; collaborative applications; Ciências Exatas e da Terra